1/5 (2x+1) -1/3 (x-2) =1/4(x-3) +1 1/2
Answers
Answered by
7
Step-by-step explanation:
1/5(2x+1) - 1/3(x-2) = 1/4(x-3) + 3/2
2x/5 + 1/5 - x/3 +2 = x/4 - 3/4 + 3/2
6x/15-5x/15 + 1/5 + 10/5 = x/4 +6/4
x/15 - x/4 = 6/4 - 11/5
4x/60 - 15x/60 = 30/20 - 44/20
-11x/60 = -15/20
-11x = -15 x 60/20
-11x = -45
x = 4.090909....
Answered by
4
Step-by-step explanation:
hope it is helpful to you and please follow me
Attachments:
![](https://hi-static.z-dn.net/files/d72/8e573a0acd38821c7284bedd73ee3d0a.jpg)
Similar questions